Safety testing the alarm close others' responses to personal positive events. [article]. - Gable, Shelly L.
Previous research has shown that receiving social support in the face of negative events (i.e. enacated support) is sometimes correlated with positive outcomes, sometimes unrelated tooutcomes, and sometimes associated with negative outcomes. However, poeple's perception that they have high-quality support available to them when they have a stressor (i.e. perceived support) is consistently and strongly associated with better health, well-being, and relationship functioning. However, both enacted and perceived support available in response to positive event disclosures are consistently associated with positive outcomes. In 2 studies, we examined why enacted support for positive events; a third study examined how support for positive events may be a major contributor to perceived availability of effective support for negative events. The results showed that providing responsive support to negative events is particularly difficult; received support for negative events disclosures (but not positive event disclosures) involves substantial drawbacks and risks, especially when that support is not responsive to the recipients' needs, and that support for stressors than enacted support for negative events. Findings are discussed in terms of implications for the social support literature and how positive relationship processes influence health and well-being, not only directly but also indirectly by providing critical information regarding the availability of others if a problem occurs. -(from the authors)